Perceived Unmet Needs and their Predictors Among Caregivers of Children with Disabilities at Community-Based Rehabilitation Centres in Selangor, Malaysia. - Sidek, Suriati (2011)
Prevalence of children with disabilities in Malaysia is increasing from year to year. Caregivers may experience the need for information, social support, a range of services and financial support in caring for these children. However, some of these needs are unmet. The aim of the study was to determine the perceived unmet needs among caregivers of children with disabilities and to identify the predictors of these unmet needs. A cross-sectional study was carried out among a total of 288 caregivers, who were recruited from 12 Community-based Rehabilitation centres in Selangor. The unmet needs were assessed using Family Needs Survey (FNS), which included six subscales of need such as information, support, community services, explaining to others, financial support and family functioning. Data on caregiver’s socio-demographic characteristics, child’s demographic characteristics, child’s functional status, family social support and perceived family burden were assessed as well in order to identify the predictors of unmet needs. All of the respondents were female with majority of them were mothers (97.2%). More than half of the respondents have children with learning disability. Caregivers identified the need for information that the child might receive in the future as their greatest need (94.4%) and the lowest was the need for getting more counseling or help in getting a job (16.3%). Out of six subscales of FNS, the need for information had the highest rating which was 98.3%, followed by need for support (93.4%), need for community services (84.0%), need for financial support (79.9%), need for family functioning (61.8%) and need to explain to others (46.2%). The mean of the overall score of unmet need was 18.67 (±SD 7.623). In multiple linear regression analysis, the results significantly showed that the predictors for the overall unmet needs were family social support, perceived family burden, occupation and education level. Predictors that were significant for the unmet needs varied in each subscale of FNS. The significant predictors for the unmet needs in the subscale of information need were family social support, occupation and education level. For the subscale of support need, the significant predictors were family social support, perceived family burden, occupation and education level. For the subscale of need to explain to others, the significant predictors were family social support, perceived family burden, education level and relationship between the caregivers and children. The significant predictor for the unmet needs in the subscale of community services need was caregivers’ occupation. For the subscale of financial support need, the significant predictors were family social support, perceived family burden, child’s functional status, occupation, family average monthly income and type of child’s disability. The significant predictors of the unmet needs in the subscale of family functioning were family social support, perceived family burden, occupation, marital status and race. As a conclusion, identification of the unmet needs of caregivers provide vital information for the development and enhancement of more effective intervention program for the caregivers in order to allow them to provide better care for their children with disabilities.